Fixed point theorems and convergence theorems for Suzuki-generalized nonexpansive mappings in CAT(0) spaces - Nanjaras,B. (Elsevier BV, 2015)
Let K be a nonempty subset of a metric space. A mapping T : K → K is said to satisfy condition (C) (sometimes called Suzuki-generalized nonexpansive) if frac(1, 2) d (x, T x) ≤ d (x, y) implies d (T x, T y) ≤ d (x, y) for all x, y ∈ K . In this paper, we obtain fixed point theorems and convergence theorems for such mappings in a CAT(0) space setting. Our results extend and improve many results in the literature. © 2009 Elsevier Ltd. All rights reserved.